Effectiveness of Combined Whole-Body Vibration and Intensive Therapeutic Exercise on Functional Capacity in Children with Cerebral Palsy: A Randomized Controlled Trial - Iñigo Monzón-Tobalina; Rosa María Ortiz-Gutiérrez; Ángela Concepción Álvarez-Melcón; Álvaro Pérez-Somarriba; Patricia Martín-Casas; María José Díaz-Arribas (Medicina)
Background and Objectives: Whole-body vibration (WBV) therapy presents controversial evidence regarding its effectiveness in improving lower limb functional capacity in children with cerebral palsy (CP), particularly when applied continuously as an adjunct to a physiotherapy program with demonstrated efficacy. This study aimed to evaluate the effectiveness of adding WBV to an intensive therapeutic exercise and functional training program in improving lower limb functional capacity in children with spastic CP. Materials and Methods: Thirty children with spastic CP were randomly assigned to a control or experimental group. Both groups completed a 4-week intensive therapeutic exercise and functional training program (4 sessions/week). The experimental group additionally received daily WBV. Results: Both groups showed significant improvements in all analysed variables at 1, 2, and 6 months post-treatment (p < 0.001). However, no significant between-group differences were found for primary (GMFM-88 D: p = 0.80; GMFM-88 E: p = 0.91) or secondary outcomes in relation to muscle tone and strength, and balance. A trend toward greater improvement was observed in the experimental group but without statistical significance. Conclusions: The addition of WBV to an intensive program of therapeutic exercise and functional training does not yield additional benefits in motor function, spasticity, gait capacity, lower limb muscle strength, or balance compared to intensive physiotherapy and functional training alone in children with spastic CP. The significant within-group improvements can be attributed to the intensive physiotherapy intervention, comprising therapeutic exercises and functional training.